2004
DOI: 10.1099/jmm.0.45643-0
|View full text |Cite
|
Sign up to set email alerts
|

Common oligosaccharide moieties inhibit the adherence of typical and atypical respiratory pathogens

Abstract: Intervention in bacterial adhesion to host cells is a novel method of overcoming current problems associated with antibiotic resistance. Antibiotic-resistant strains of bacteria that cause respiratory tract infections are a problem in hospitals and could be used in bioterrorist attacks. A range of bacterial species was demonstrated to attach to an alveolar epithelial (A549) cell line. In all cases, cell surface oligosaccharides were important in attachment, demonstrated by reduced adhesion when A549 cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 56 publications
3
83
1
3
Order By: Relevance
“…Attachment of bacteria to host cells is one of the key steps of infection and often relies on an interaction between bacterial adhesins and oligosaccharides on the host cells. These interactions are usually mediated by binding of lectins present on the bacterial surface to oligosaccharide chains bound to glycoproteins and glycolipids on eukaryotic cells (Thomas & Brooks, 2004). This is probably also the case for M. pneumoniae attachment, since reduced adhesion of M. pneumoniae has been demonstrated when human alveolar epithelial cells (A549) are pre-treated with tunicamycin, which degrades oligosaccharides (Thomas & Brooks, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attachment of bacteria to host cells is one of the key steps of infection and often relies on an interaction between bacterial adhesins and oligosaccharides on the host cells. These interactions are usually mediated by binding of lectins present on the bacterial surface to oligosaccharide chains bound to glycoproteins and glycolipids on eukaryotic cells (Thomas & Brooks, 2004). This is probably also the case for M. pneumoniae attachment, since reduced adhesion of M. pneumoniae has been demonstrated when human alveolar epithelial cells (A549) are pre-treated with tunicamycin, which degrades oligosaccharides (Thomas & Brooks, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions are usually mediated by binding of lectins present on the bacterial surface to oligosaccharide chains bound to glycoproteins and glycolipids on eukaryotic cells (Thomas & Brooks, 2004). This is probably also the case for M. pneumoniae attachment, since reduced adhesion of M. pneumoniae has been demonstrated when human alveolar epithelial cells (A549) are pre-treated with tunicamycin, which degrades oligosaccharides (Thomas & Brooks, 2004). In addition, other studies have shown that the adhesion of M. pneumoniae to tracheal epithelial cells decreases by 50-65 % when they are treated with neuraminidase, which cleaves terminal acylneuraminic residues from oligosaccharides, glycoproteins and glycolipids.…”
Section: Introductionmentioning
confidence: 99%
“…The plague pathogen demonstrates a restricted tropism for oligosaccharides compared with environmental and opportunistic bacteria. It has been shown that the compound with the greatest anti-adhesion activity toward A549 cells is pnitrophenol (Thomas & Brooks, 2004). As an alternative to antibiotics, the inhibition of attachment can be mediated through the use of oligosaccharide receptor mimics.…”
Section: Inhibitors Of Virulence Factorsmentioning
confidence: 99%
“…This further demonstrates the potential of oligosaccharides as anti-adhesion therapeutics. Other generic attachment inhibitors include polymeric saccharides (dextran and heparin), GalNAcb1-4Gal, GalNAcb1-3Gal, Galb1-4GlcNAc and Galb1-3GlcNAc (Thomas & Brooks, 2004). It is possible that mixtures of such compounds may serve as a novel class of therapeutics for respiratory tract infections, including pneumonic plague.…”
Section: Inhibitors Of Virulence Factorsmentioning
confidence: 99%
“…Clinical and experimental models have demonstrated that heparin or other anti-coagulants reduce fibrin deposition in the lungs and improve clinical outcomes [13][14][15][16][17]. Heparin has other actions, including reduced pulmonary edema, reduced leukocyte activation, and inhibition of adhesion of bacteria and viruses to respiratory surfaces, that may also be beneficial [18][19][20][21][22]. Evidence from large, multi-center, clinical studies in patients with severe sepsis also suggests that heparin may improve important clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%